Straight talk - Bowen, Charles; Schneider, J. Stewart (New York : Bantam Books, 1989)
A communications program tailored specifically to real-time conferencing. Features include intelligent pull-down menus, a library of ready-to-run macro sets that "standardize" commands among the five top on-line talk facilities, and a data base-style notebook, among others.
Title from t.p. of book.
Keywords: Telecommunication; Computer conferencing